Formulasi Dan Uji Mutu Fisik Masker Gel Peel Off Kombinasi Sisik Ikan Bandeng Dan Kulit Jeruk Nipis - Cikra Ikhda Nur Hamida Safitri; Elly Purwati; Khoirunnisa Fibrianti (An-Najat, 2024)
Lime contains flavonoids which have antioxidant properties by inhibiting free radicals. Meanwhile, milkfish scales contain 0,3% collagen which can be used as anti-aging for skin. Bot function as skon care products with an alternative formulation into a peel off gel mask. The aim of this research is to determine whether a combination of milkfish scale powder and lime peel can be formulated into a peel off gel mask. The method used is an experimental method by immersion extraction in 70% ethanol solvent. The formulation of milkfish scales is 1%, 3%, and 5%. Lime extract uses 0,6%; 1,2%; and 1,8%. Evaluation of physical quality in accordance with SNI masks 16-6070-1999. The results showed that the three formulations were not homogeneous due to the presence of insoluble fish scale powder, there was no changes in the organoleptic test parameters, the pH test range (4 -6), the test range spreadability of (3,7 – 7,5 cm), dry time (15 minutes), and viscosity test (1189 mPa.S-3598 mPa.S). The conclusion of this research is that lime peel and milkfish scales can be formulated as active ingredients for peel off gel masks and the physical quality test of peel off gel mask preparations meet the requirements.